DINAMIKA PERTUMBUHAN UMKM DAN PERDAGANGAN INFORMAL DALAM MEMENUHI KEBUTUHAN LOKAL SERTA LINTAS BATAS: KENDALA AKSES MODAL DAN PASAR - S Pentanurbowo; Al-Amin (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study discusses the dynamics of Micro, Small and Medium Enterprises (MSMEs) and informal trade in meeting local and cross-border needs, with a focus on barriers to capital and market access. MSMEs and the informal sector have proven to play an important role in supporting the national economy, particularly in providing employment and meeting the daily needs of the community. However, this significant contribution is still hampered by various structural challenges, including limited access to formal capital sources, low financial literacy, limited distribution, and difficulty penetrating modern and cross-border markets. The study uses a literature review method by analysing literature from various sources to summarise the growth patterns, main obstacles, and development opportunities of both sectors. The results of the study show that although MSMEs and informal trade have high adaptability, they need inclusive policy support, the use of digital technology, and network strengthening strategies to expand access to capital and markets. With these measures, MSMEs and informal trade have the potential to become more competitive, globally competitive, and able to contribute significantly to sustainable economic development.